Awareness of Knowledge Management in Nepalese Financial Institutions - Khanal, Lekhanath (Journal of Advanced Academic Research, 2017)
Knowledge Management (KM) is one of the buzzwords prevailing in the management circles. It is seen as a tool which can create a strategic impact. Organizations which are unaware of knowledge management (KM) and its concepts are considered illiterate in business context. In order to thrive in this turbulent market, an organization must be familiar with all concepts pertaining to its intellectual assets, i.e. Knowledge, and all other activities involved in managing its intangible assets, i.e. KM through various practices, suitable strategy and processes,. Banks and financial institutions as drivers of economic growth play a major role in prosperity and innovativeness of almost all countries worldwide. The main objective of this study is to identify the awareness of knowledge management in financial institutions of Nepal. In this study, samples of 385 respondents were selected randomly from four different types of financial institutions of Kathmandu, Nepal. The statistical analysis was done to draw the conclusion. The results clearly show that the level of KM awareness amongst Nepalese financial institutions is medium in which some companies understand the principles of KM but they observe many challenges and difficulties in pursuing KM implementation. Finally, this paper concludes that those institutions which are aware of the basic concepts and principle of KM can effectively manage knowledge resources; are more innovative and have better performance than others who do not takes this factor into account.Journal of Advanced Academic Research, Vol. 3, No. 3, 2016